Measurements and Analysis of Potential Oscillations Near the Hollow Cathode. (2017) - Qin, Yu; Xie, Kan; Ouyang, JiTing
Abstract: We investigated the potential oscillations near a hollow cathode for ring-type anode configuration and planar disc anode configuration using diagnostic tools. The waveform of potential oscillations, amplitude of plasma potential and ion density were measured. The plasma potential oscillations show rapid rising but slow decrease. The results show that ionization in a ring-type anode is more effective than that in a planar disc anode and the amplitude of plasma potential in a ring-type anode is much larger than that in a planar disc anode at the same operating conditions. The highest amplitude of plasma potential that occurred corresponds to the area where the highest ion density appeared for both anode configurations, which shows that xenon ions in space play an important role for this kind of plasma potential.